Leporid immunoglobulin G shows evidence of strong selective pressure on the hinge and CH3 domains. Issue 9 (September 2014) - Pinheiro, Ana; Woof, Jenny M.; Almeida, Tereza; Abrantes, Joana; Alves, Paulo C.; Gortázar, Christian; Esteves, Pedro J.
Abstract : Immunoglobulin G (IgG) is the predominant serum immunoglobulin and has the longest serum half-life of all the antibody classes. The European rabbit IgG has been of significant importance in immunological research, and is therefore well characterized. However, the IgG of other leporids has been disregarded. To evaluate the evolution of this gene in leporids, we sequenced the complete IGHG for six other genera: Bunolagus, Brachylagus, Lepus, Pentalagus, Romerolagus and Sylvilagus . The newly sequenced leporid IGHG gene has an organization and structure similar to that of the European rabbit IgG. A gradient in leporid IgG constant domain diversity was observed, with the CH1 being the most conserved and the CH3 the most variable domain. Positive selection was found to be acting on all constant domains, but with a greater incidence in the CH3 domain, where a cluster of three positively selected sites was identified. In the hinge region, only three polymorphic positions were observed. The same hinge length was observed for all leporids. Unlike the variation observed for the European rabbit, all 11 Lepus species studied share exactly the same hinge motif, suggesting its maintenance as a result of an advantageous structure or conformation.